Enantioselective synthesis of multi-nitrogen-containing heterocycles using azoalkenes as key intermediates. Issue 47 (28th May 2019) - Wei, Liang; Shen, Chong; Hu, Yuan-Zhen; Tao, Hai-Yan; Wang, Chun-Jiang
Abstract : The recently developed annulation reactions using azoalkenes as key intermediates show their great ability to construct diverse types of multi-nitrogen-containing heterocycles. In this feature article, we critically analysed the strategic development and the efficient transformation of azoalkenes to chiral heterocycles and α-functionalized ketone derivatives since 2010. Abstract : Chiral multi-nitrogen-containing heterocycles, such as pyrazole, imidazole and pyridazine, are widely found in naturally occurring organic compounds and pharmaceuticals, and hence, their stereoselective and efficient synthesis is an important issue in organic synthesis. Out of the variety of methods that have been developed over the past century, the catalytic asymmetric cyclization and cycloaddition reactions are recognized as the most synthetically useful strategies due to their step-, atom- and redox-economic nature. In particular, the recently developed annulation reactions using azoalkenes as key intermediates show their great ability to construct diverse types of multi-nitrogen-containing heterocycles. In this feature article, we critically analyse the strategic development and the efficient transformation of azoalkenes to chiral heterocycles and α-functionalized ketone derivatives since 2010. The plausible mechanism for each reaction model is also discussed.